Overview on ontology mapping and approach - Xiyin Liu; Lijun Cao; Wei Dai (2011 4th IEEE International Conference on Broadband Network and Multimedia Technology, 2011)
This paper begins with the concept of ontology and ontology mapping. On ground of the description of ontology, classification on similarity is given in this paper. They include the approaches based on syntax, instance, constraint, architecture and property relations. And the mapping approaches are also classified according to the mapping technique, such as approaches based on logic inference, statistic, machine learning, graph theory, information flow, modularization, fuzzy conceptual graph, risk decision and formal conceptual analysis. Meanwhile each approach is described briefly. The existing problems and prospect are proposed at last.